High responsive microwave resonator sensor for material characterization - Meor Said, Maizatul Alice; Mohammed Ba Amer, Rayan Ahmed; Mohideen Ghani, Muhammad Syaheer; Misran, Mohamad Harris; Othman, Mohd Azlishah; Suhaimi, Shadia; Hassan, Nurmala Irdawaty (Human Resource Management Academic Research Society, 2024)
This work describes the planning and execution of a planar microwave resonator sensor for a sensing application based on the perturbation idea, in which the quality factor (QF) and the resonance frequency are affected by the resonator's dielectric properties. The FR4-made sensor operates at 2.4 GHz in the ranges of 1-3 GHz, and it was designed for use in testing solids. In addition, real-world materials like those found in Roger 5880 and FR4 are employed as sample materials in experiments that follow a particular experimental design. The functionality of the microwave resonator sensor is studied by introducing an equivalent circuit model (ECM). The suggested sensor has a QF value of 239 at its optimum operating frequency of 2.4GHz, with a narrow bandwidth. Additionally, the sensor's sensitivity and accuracy are both higher than 80%, making it a great option for characterizing the material, particularly for determining its qualities and traits.